Effect of various hormones on red cell production in mice - Haber, C.; Firat, D.; Leff, S. (The Turkish Journal of Pediatrics, 1972)
The effect of various hormones on red cell production in mice has been studied using protein deprived CFI adult female mice. Fe59 incorporation into circulating red cells was used as an index of the erythropoiesis.The majority of the hormones had a stimulatory effect on red cell production of mice when injected for 2 days. However only androgens, TSH, growth hormone and prolactin demonstrated a sustained effect when injected daily for longer period of time. Their erythropoietic effects appeared to be mediated via stimulation of erythropoietin production.